Penerapan Strategi Kooperatif Learning Tipe STAD Dalam Meningkatkan Kecerdasan Sosial Peserta Didik di SMP Negeri 4 Simbang Kecamatan Pamboang Kabupaten Majene - Jufri; Hasriah (Tamilis Synex: Multidimensional Collaboration, 2025)
This thesis discusses the implementation of the STAD Type Cooperative Learning strategy in improving the social intelligence of Class VII students. A at SMP Negeri 4 Simbang, Pamboang District, Majene Regency. The main problems studied focused on how to apply cooperative learning strategies, social intelligence, strengths and weaknesses that aim to find out the process of implementing the cooperative learning learning model from beginning to end and describe students' social intelligence after its implementation. As a complement to this thesis, the author uses the type of Classroom Action research, with a qualitative descriptive approach. Research on disclosing problems as they exist is data analysis using field research, observation, interviews, and documentation using data analysis, namely, data presentation, data reduction, and drawing conclusions (verification). The results of this study indicate that the implementation of PAI learning on the STAD Type Cooperative Learning strategy in SMP Negeri 4 Simbang class VII A. Well implemented, effective and efficient, fun and exciting. Have a positive impact on students in learning. There are several advantages in the application of Cooperative Learning learning strategies including fun, confident, responsible, interest in learning and creative thinking. Some of these factors are interrelated or have a relationship and need and complement each other. Then the shortcomings that occur in the application of cooperative learning strategies include excessive pleasure, lack of skills and limited learning resources.